PENGARUH MEDIA SMART BOX TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SD NEGERI 216 TALUNGENG - Sudarto, Sudarto; Muhammad Amin; Suriana, Suriana (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
This research is a Pre-Experimental research which aims to find out whether there is or not a significant influence of the implementation of Smart Box media on students’ science learning outcomes. The variables in this research are Smart Box media (independent variable) and science and science learning outcomes (dependent variable). The population of this study was all of the fourth grade students at SD Negeri 216 Talungeng with a sample of 23 students selected based on a saturated sampling technique. The data collection technique used was a test technique with data analysis techniques using descriptive and inferential statistics. Based on the results of descriptive statistical analysis, the pretest average was of 43.04 (in the poor category) and the pottest average was 78.04 (in the good category). Meanwhile, based on inferential analysis it was obtained: the sig (2-tailed) value of 0.000 is smaller than 0.05 and H1 is accepted. Conclusion: because the posttest average is greater than the pretest average and H1 was accepted, which means there was a significant difference between science learning outcomes before and after using Smart Box media, it can be concluded that there was a significant influence between the implementation of Smart Box learning media on IPAS learning outcomes for the 4th Grade students at SD Negeri 216 Talungeng, Barebbo District, Bone Regency